Bullitt [videorecording (DVD)] - Yates, Peter, 1929-2011; McQueen, Steve, 1930-1980; Vaughn, Robert, 1932-2016; Bisset, Jacqueline, 1944-; Pike, Robert L., 1912-1981 (Warner Home Video, 2010)
When the star witness under his protection is shot, cop Frank Bullitt becomes determined to find the criminal who injured him.